HUBUNGAN ANTARA QUALITY OF WORK LIFE DENGAN TURNOVER INTENTION - Rosita Oliviani; Laurentia Verina Halim Secapramana; Listyo Yuwanto (Perpustakaan Universitas Surabaya, 2021)
Abstract — Turnover intention is the employees’s intention to leave a company at this time. Turnover intention becomes one of the predictor that causing turnover. A high rate of the turnover will impact the company’s expenses for the recruitment and selection of the new employees, also will impact the social instability of a company. This research used quantitative correlational study with survey or questionnaire approached. The samples are calculated using the raosoft application. The data were collected from 194 employees at PT. X in Pasuruan, East Java. The sampling technique using accidental sampling that adjusted to the criteria of this research, such as employees aged around 20 – 60 years and have worked for at least 1 year. Turnover intention measured by turnover intention scale by Mobley et al (1979), while quality of work life measured by EWON Scale (2002) and open questions. Data analysis in this study is using the SPSS 22.0 application. The results of the analysis show that there is a relationship between quality of work life and turnover intention (r = -0.279, p <0.05). The correlation shows that the quality of work life can improve employee performance and higher productivity so it will reduce the intention to leave from the company. Job security became the aspect that had the highest correlation value with turnover intention (r = -0.313, p <0.05). Based on the results, implications for the company are increase or maintain the level of quality of work life . For further research, it is expected to increase the variation of open questionnaires to get other factors that affect the quality of work life. Keywords: quality of work life, turnover intention Abstrak— Turnover intention adalah niat karyawan untuk keluar dari suatu perusahaan saat ini. Turnover intention menjadi salah satu prediktor terjadinya turnover. Tingkat turnover yang tinggi akan berdampak pada pengeluaran biaya perusahaan yang semakin besar guna perekrutan dan seleksi karyawan baru serta akan berdampak pada ketidak stabilan kondisi sosial suatu perusahaan. Penelitian ini menggunakan penelitian korelasional kuantitatif dengan pendekatan survei atau kuesioner. Perhitungan sampel menggunakan aplikasi raosoft. Data dikumpulkan dari 194 karyawan di PT. X di Pasuruan, Jawa Timur. Teknik pengambilan sampel menggunakan accidental sampling yang disesuaikan dengan kriteria penelitian ini, yaitu karyawan berusia sekitar 20 - 60 tahun dan telah bekerja minimal selama 1 tahun. Intensi keluar dari perusahaan diukur dengan skala dari Mobley et al (1979) sedangkan kualitas kehidupan kerja diukur dengan Skala EWON (2002), dan pertanyaan terbuka. Analisis data dalam penelitian ini menggunakan aplikasi SPSS 22.0. Hasil penelitian menujukkan bahwa ada hubungan antara quality of work life dengan turnover intention (r = -0,279, p< 0.05). Job security menjadi aspek yang memiliki nilai korelasi tertinggi dengan turnover intention (r = - 0,313, p< 0.05). Korelasi tersebut menunjukkan bahwa subjek menganggap bahwa kualitas kehidupan pekerjaan menjadi salah satu hal yang dapat meningkatkan kinerja dan produktivitas karyawan yang lebih tinggi sehingga hal itu akan mengurangi adanya intensi keluar yang dimiliki oleh karyawan. Implikasi bagi perusahaan adalah perusahaan dapat meningkatkan atau mempertahankan tingkatan quality of work life. Bagi penelitian selanjutnya dapat menambah variasi angket terbuka untuk mendapatkan faktor lain yang memengaruhi kualitas kehidupan pekerja. Kata kunci: kualitas kehidupan kerja, intensi keluar